Estimation of serum calcium levels in apheresis platelet donors - P. Arpitha; Ravindra Prasad Thokala (Asian Journal of Transfusion Science)
INTRODUCTION: Apheresis is practiced widely to collect single donor platelets (SDPs). This procedure utilizes an anticoagulant acid citrate dextrose to prevent clotting of blood in the extracorporeal circuit which chelates divalent ions like calcium. This alters the calcium homeostasis resulting in hypocalcemia causing acute adverse events. AIM: The study aimed to know the calcium homeostasis in apheresis platelet donors. MATERIALS AND METHODS: This cross-sectional study was conducted from January 2020 to December 2020 in the department of transfusion medicine. The sample size was 50. Donors who walk in for voluntary SDP donation were selected. Total and ionized calcium, pH, and serum albumin for all the donors at baseline and ionic calcium at the end of the procedure and 30 min after the procedure were measured. RESULTS: According to statistical analysis of the ionic calcium level at pre procedure, immediate post procedure and 30 minutes post procedure, there was decrease in the value immediate post procedure and values returned to baseline within 30 minutes. The levels of pH change were analyzed. On comparing the preprocedure and immediate postprocedure values, there was a significant lowering of pH value from the baseline (P = 0.5), indicating acute lowering of pH immediate postprocedure. Hence, most of the citrate metabolism can be achieved within 30 min after completion of the apheresis procedure. CONCLUSION: SDP collection is essentially a safe procedure with minimal adverse effects. Toxicity of citrate is not much pronounced. Recovery of calcium levels is within 30 min of completion of plateletpheresis.